"Burning the Judas": the fete as a geographical event (Huellas, 2019)
In the city of Luján, daily spatiality is built with great influence from the religious sphere. The city itself could be considered as the main seat of the Marian Catholic cult nationwide and visitors exceeding one million people annually is a clear evidence of this fact. Although it is not a practice with current origins (the first manifestations in Lujan are recorded in the colonial period) the fete of the Burning of Judas has experienced in recent years a new series of modifications around the morphology of the celebrations. During the first decade of the current century, the municipal government implemented a series of devices aiming at institutionalizing this holiday in order to include it in Luján “tourist agenda”. This situation opened a new space for disputes over the festivity, which is now formally known as the “Colonial Easter”. From a Cultural Geography perspective, this article proposes to carry out a theoretical discussion about the main conceptualizations thought as tools for a critical approach to the festive stages. The analytical categories of scenario, territoriality, fete, among others, are some of the concepts considered nodal to carry out the research.
Keywords: Fete; culture; stage; territory; Colonial Easter.